Development of Certain Protein Kinase Inhibitors with the Components from Traditional Chinese Medicine - Liu, Minghua; Zhao, Ge; Cao, Shousong; Zhang, Yangyang; Li, Xiaofang; Lin, Xiukun (Frontiers in Pharmacology, 2017)
Abstract: Traditional Chinese medicines (TCMs) have been used in China for more than two thousand years, and some of them have been confirmed to be effective in cancer treatment. Protein kinases play critical roles in control of cell growth, proliferation, migration, survival and angiogenesis and mediate their biological effects through their catalytic activity. In recent years, numerous protein kinase inhibitors have been developed and are being used clinically. Anticancer TCMs represent a large class of bioactive substances, and some of them display anticancer activity via inhibiting protein kinases to affect the phosphoinositide 3-kinase, serine/threonine-specific protein kinases, pechanistic target of rapamycin (PI3K/AKT/mTOR), P38, mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinases (ERK) pathways. In the present article, we comprehensively reviewed several components isolated from anticancer TCMs that exhibited significantly inhibitory activity towards a range of protein kinases. These components, which belong to diverse structural classes, are reviewed herein, based upon the kinases that they inhibit. The prospects and problems in development of the anticancer TCMs are also discussed.